2023
DOI: 10.3389/fpubh.2022.1064896
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety knowledge, attitude and practice among undergraduate health science students in South West Ethiopia

Abstract: BackgroundPatient safety is minimizing the risk of unnecessary damage associated with healthcare to a minimum. It has been linked as a global precedence area where substantial knowledge gaps exist. Knowledge, attitude, and practice of the healthcare providers toward patient safety have a great influence on the delivery of safe patient care. Regardless of this, the issue has not been adequately addressed in Ethiopia.ObjectiveThe main aim of this study was to assess the knowledge, attitude, practice, and factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
1
Order By: Relevance
“…The study also reported that only 19.9% of the participants had good patient safety practices. Duration of clinical exposure, year of study and knowledge on patient safety were linked with good patient safety practices (8) . Another study conducted among nurses in Ethiopia also reported that only 48.4% of the participants had good knowledge on patient safety and 56.1% had favourable attitude towards patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also reported that only 19.9% of the participants had good patient safety practices. Duration of clinical exposure, year of study and knowledge on patient safety were linked with good patient safety practices (8) . Another study conducted among nurses in Ethiopia also reported that only 48.4% of the participants had good knowledge on patient safety and 56.1% had favourable attitude towards patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge and duration of clinical exposure of nursing students were found to be the factors influencing patient safety practices. It is recommended that education programs for healthcare professionals incorporate essential patient safety content and language to enhance their abilities in safeguarding patients (8). Promoting patient safety within healthcare organisations can be achieved through collaborative teamwork, effective communication, and a comprehensive set of measures aimed at preventing errors.…”
Section: Introductionmentioning
confidence: 99%
“…Kết quả này tương đồng với các nghiên cứu được thực hiện trước đây. Cụ thể theo nghiên cứu của Mohammed thực hiện trên 678 sinh viên tại Ethiopia chỉ có 293 sinh viên (chiếm 43,2%) có kiến thức tốt về an toàn người bệnh [5]. Tương tự, theo nghiên cứu của Jones và cộng sự thực hiện nhằm mục tiêu đánh giá kiến thức của sinh viên điều dưỡng về an toàn người bệnh, với 2011 sinh viên năm cuối tại Úc và New Zealand tham gia, kết quả nghiên cứu cho thấy rằng khoảng một nửa sinh viên điều dưỡng có kiến thức tốt về an toàn người bệnh và kiến thức này tăng dần theo kinh nghiệm thực hành lâm sàng của sinh viên [6].…”
Section: Kiến Thức Về An Toàn Người Bệnh Của Sinh Viên đIều Dưỡng Và ...unclassified